The Art Of Calligraphy In A Review Of Islamic Education - Zakiah Mardiah Nasution; Sri Harni (Jurnal Eduslamic, 2023)
Art is something that cannot be separated from human life, as well as the art of calligraphy. Calligraphy is the most interesting art in the Islamic world. This is because the magnificence that is created does not eliminate the value of monotheism in Allah Swt, because it is guided by the Al-Quran. It is this foundation that makes The Researcher want to examine this discussion. The magnitude of the influence of calligraphy brings and guides Researchers to examine this discussion with a qualitative method. The technique used is literature study data collection based on relevant references. The purpose of this study is to find out how the art of calligraphy is reviewed in Islamic education, so based on the research obtained it is stated that the art of calligraphy is very influential in Islamic education, and the form of its application can increase moral values ​​in oneself.